2019
DOI: 10.1038/s41598-018-38407-4
|View full text |Cite
|
Sign up to set email alerts
|

Flexible PVC materials grafted with castor oil derivative containing synergistic flame retardant groups of nitrogen and phosphorus

Abstract: Internally plasticized PVC by replacement of chlorine with castor oil derivative containing synergistic flame retardant groups of nitrogen and phosphorus, that is, castor oil derivative grafted onto PVC matrix, is reported. Low glass transition temperature (Tg) of modified PVC was produced although thermal stability was reduced. However, the migration was completely suppressed. The combination of castor oil derivative containing synergistic flame retardant groups of nitrogen and phosphorus with PVC matrix thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“… 25 29 To prevent the migration of the plasticizers, vegetable oil-based compounds were also covalently attached to PVC via azide–alkyne click reactions. 30 32 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 25 29 To prevent the migration of the plasticizers, vegetable oil-based compounds were also covalently attached to PVC via azide–alkyne click reactions. 30 32 …”
Section: Introductionmentioning
confidence: 99%
“…Aside from these direct uses of vegetable oils for the preparation of plastic materials, lately, derivatives of vegetable oil have been used as additives or agents for a wide range of applications including the modification of commercial polymers. Vegetable oils were used as plasticizers, lubricants, stabilizers, processing aids, surfactants, etc. Especially, much effort has been devoted to the use of vegetable oils as plasticizers, particularly for polyvinyl chloride (PVC). To prevent the migration of the plasticizers, vegetable oil-based compounds were also covalently attached to PVC via azide–alkyne click reactions. …”
Section: Introductionmentioning
confidence: 99%
“… 18 22 However, these plasticizers also have some drawbacks that need to be addressed, such as low compatibility with PVC, low plasticization efficiency and poor heat stability due to the aliphatic structure, and higher molar mass compared to phthalate plasticizers. 23 Among renewable plasticizers, phosphorus-containing bioplasticizers can enhance the thermal stability, 24 and the aromatic group in bioplasticizers can improve the compatibility of the plasticizer with PVC. 5 , 25 The biobased cardanol oil isolated from cashew nut shell liquid can act as an epoxy curing agent and as a plasticizer.…”
Section: Introductionmentioning
confidence: 99%
“…Given the adverse effects of DOP and depletion of petroleum resources, biobased plasticizers have attracted growing academic and industrial interests, including vegetable oils, succinic acid, citric acid, fatty acid, and isosorbide. However, these plasticizers also have some drawbacks that need to be addressed, such as low compatibility with PVC, low plasticization efficiency and poor heat stability due to the aliphatic structure, and higher molar mass compared to phthalate plasticizers . Among renewable plasticizers, phosphorus-containing bioplasticizers can enhance the thermal stability, and the aromatic group in bioplasticizers can improve the compatibility of the plasticizer with PVC. , The biobased cardanol oil isolated from cashew nut shell liquid can act as an epoxy curing agent and as a plasticizer. The use of cardanol as the primary or secondary plasticizer can enhance the flexibility and thermal stability and decrease the volatility of PVC materials. It has also been suggested that some renewable plasticizers have good leaching resistance, plasticization efficiency, and excellent thermal stability …”
Section: Introductionmentioning
confidence: 99%
“…The chemical compounds such as metal alloys, coordination compounds, inorganic and organic compounds are preferred as flame retardants for PVC [5][6][7][8]. Inorganic fillers which are alumina trihydrate (ATH) and magnesium hydroxide (MH) play a dual role as flame retardancy and mineral reinforcement [9].…”
Section: Introductionmentioning
confidence: 99%